(untitled) (Global Journal of Management and Business Research, 2011)
One of the major concerns of Indian Planning has been the removal of disparities among different sections of population especially the weaker sections like the scheduled tribes and scheduled castes. The basic features common to these tribes as listed in the constitution were that they were having tribal origins, primitive ways of life, habitation in remote and less easily accessible areas and generally backward- socially and economically. The main objective is to analyse the present socio-economic conditions of the tribals in the district and to find out the innovative schemes for Human Resources Development by way of education, training and other social facilities to the tribals of Orissa in India.